2003
DOI: 10.1021/jp034020+
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule LEDs from Nanoscale Electroluminescent Junctions

Abstract: Through pulsed operation, polarity is introduced in single Ag nanocluster (Ag 2 -Ag 8 ) electroluminescence within seemingly nonpolar two-terminal nanoscale break junctions at room temperature. While observable with much higher power DC excitation, both high-frequency pulsed and AC operation lead to greatly increased spectrally and thermally stable electroluminescence with much narrower individual nanocluster electroluminescence spectra. Being polarity independent under both sinusoidal and DC excitations, puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Similar to our results involving silver [26], these gold junctions operate with overall asymmetry in emission and demonstrate weak light-emitting diode behavior due to preferential electron injection through the anode. The ensemble (multiparticle) g 2 [ Fig.…”
Section: Fig 1 Schematic Of Hanburysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to our results involving silver [26], these gold junctions operate with overall asymmetry in emission and demonstrate weak light-emitting diode behavior due to preferential electron injection through the anode. The ensemble (multiparticle) g 2 [ Fig.…”
Section: Fig 1 Schematic Of Hanburysupporting
confidence: 83%
“…Recently, we created a new class of noble metal quantum dots that exhibit strong fluorescence in aqueous solution [21,24], as well as electroluminescence within deposited films [25,26]. Behaving as multielectron artificial atoms, these nanogold species should provide facile routes to producing strong single-photon emitters, even approaching telecommunication wavelengths.…”
mentioning
confidence: 99%
“…In contrast, easier hole injection from the anode to the emitting layer was expected for PBPV than for the other two. These results demonstrated that easier electron injection to the emitting layer was more crucial for better device performance than hole injection, which has been ascertained by many other scientists 19–21. In addition, Figure 5 shows that fluorescence decay in films (70–90 nm thick) was fastest for PBPV and slowest for P(DOF‐PVP).…”
Section: Resultssupporting
confidence: 56%
“…12,19,20 The electromigrationinduced junctions show silver nanocluster EL with nanocluster energy levels pinned to those of the anode-a result of the asymmetric electromigration process that moves material toward the anode. 12,24,21 The heterojunction nature of the electromigration-induced junction is further understood by imaging the fluorescence from each electrode-only the anode is strongly fluorescent under blue excitation ͑450-480 nm͒, indicating different chemical compositions of the cathode and anode. Energy dispersive spectroscopy across the junction directly reveals that the oxygen content is higher on the cathode than on the anode ͑not shown͒.…”
Section: Facile On-demand Electronic Nanodevice Fabrication From Phomentioning
confidence: 99%